The advertisement call of Proceratophrys renalis (Miranda-Ribeiro, 1920) (Amphibia: Anura: Cycloramphidae) - Santana, Diego José; Rodrigues, Ricardo; de Albuquerque, Ralph Lacerda; Laranjeiras, Daniel Orsi; Protázio, Arielson Dos Santos; França, Frederico Gustavo Rodrigues; Mesquita, Daniel Oliveira (Zootaxa, 2011)
Proceratophrys renalis (Fig. 1A) was recently revalidated (Prado & Pombal 2008). This frog species comprises a population previously recognized as P. boiei. It occurs in Atlantic forest from Paraíba to south of Bahia State, and in the interior of Brazil, close to transitions between Cerrado and Caatinga biomes, including Jequitinhonha river basin in Minas Gerais State (Prado & Pombal 2008).